FUNGSI JANGGRUNG DALAM UPACARA NYADRAN DI PANTAI SLILI TEPUS GUNUNGKIDUL YOGYAKARTA - Laksono, Joko Tri (Harmonia: Journal of Arts Research and Education, 2009)
The research problems are about Nyadran ceremonial processes, functions of Janggrung in thatceremony, and special musics in Janggrung offbeat. Results and discussions: (1) Nyadranceremony can be concluded in ritual ceremony since day, time, place, head, and congregationchosen by Janggrung performance. (2) In Nyadran ceremony, Janggrung functioned as anemotional expression, an entertainment, means of communication, a symbolic representation, aphysical response, a legalization of social and ritual religion organization, to keep continuity ofculture, and as a prop of social integration. Moreover, Janggrung also functioned as extrication ofone’s vow. Janggrung dancers (tledhek) who functioned in nyadran ceremony have severalprohibition that cannot be broken, that is one of those dancers must be a virgin. (3) There are fivespecial music to accompany Janggrung those are Lung Gandhung, Sekar Gandhung, KinanthiSandhung (called Kinanti Boyong by door-keeper), Cangklek and Kebogiro Gangsaran. The Beatthat accompanies Janggrung is Javanese barreled orchestra Slendro without using garap ngajenginstrument. It is because there is no need to present lirihan instrument in Janggrung performanceinstrumentation.Kata Kunci: fungsi janggrung, upacara nyadran, fungsi gending